Independence, Competence, Objectivity, Ethics And Auditor Experience On Auditor Quality - Septi Handayani, Wuri; Kuni Khairunnisa (Jurnal Akuntansi, 2024)
This study aims to examine and analyse the influence of Independence, Competence, Objectivity, Auditor Ethics, and Auditor Experience on the Audit Quality of Auditors of Public Accountant Offices in South Jakarta in 2023. The sample in this study was an auditor who worked in 10 public Accountant Offices in South Jakarta. The sampling method used is a Purposive Sampling Method. The primary data used in this study was obtained directly from respondents. The data collection method used was a questionnaire method with 98 respondents as many respondents. Analysis of the data used is multiple linear regression analysis and using the Partial Least Square (SmartPLS) program version 3.2.9 for Windows Partial Least Square (SmartPLS) version 3.2.9 for Windows. The results of the tests showed that independence, competence, objectivity, auditor ethic, and auditor experience significantly positively affect audit quality.